Promoting effect of protecting group on the structure and morphology of self-assembled monolayers: terphenylylethanethioactate on au(111) - Bashir, Asif; Iqbal, Danish; Jain, Sagar Motilal; Barbe, Kathrin; Abu Husein, Tarek Naser; Rohwerder, Michael; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
Taking self-assembled monolayers (SAMs) of 4,4′-terphenylyl-substituted ethanethioacetate (TP2-SAc) on Au(111) as a test system, we studied the effect of the protecting group on the structure and morphology of this monolayer. The films were prepared at both room (298 K) and elevated (333 K) temperature, at either the presence or absence of a deprotecting agent, viz., triethylamine. The presence of the protecting group resulted in distinctly different crystallographic structure, described by the (2√3 × 4) rect unit cell, in all SAMs studied as compared to the case of the nonprotected analogue. The molecules within this unit cell were arranged in a herringbone fashion as could be observed by variation of the scan direction during the image acquisition by scanning tunneling microscopy. Most important and in contrast to previous studies of similar systems, the presence of the protecting group led to significant improvement of the SAM morphology in the case of preparation at 333 K, resulting in formation of comparably large domains with dimensions exceeding 100 nm. The effect of the deprotecting agent was found to be small when preparing at 298 K and hardly perceptible at 333 K. Determination of the reaction kinetics gave evidence of a completely different reaction mechanism for the thioacetate as compared to the thiol, which presumably is responsible for the observed differences.
Gesehen am 30.07.2020